Tacrolimus Protects Podocytes from Injury in Lupus Nephritis Partly by Stabilizing the Cytoskeleton and Inhibiting Podocyte Apoptosis. - Ruyi Liao; Qinghua Liu; Zhihua Zheng; Jinjin Fan; Wenxing Peng; Qingyu Kong; Huijuan He; Shicong Yang; Wenfang Chen; Xueqing Tang; Xueqing Yu (PLoS ONE, 2015)
Several studies have reported that tacrolimus (TAC) significantly reduced proteinuria in lupus nephritis (LN) patients and mouse models. However, the mechanism for this effect remains undetermined. This study explored the mechanism of how TAC protects podocytes from injury to identify new targets for protecting renal function.MRL/lpr mice were given TAC at a dosage of 0.1 mg/kg per day by intragastric administration for 8 weeks. Urine and blood samples were collected. Kidney sections (2 μm) were stained with hematoxylin-eosin (HE), periodic acid-Schiff base (PAS) and Masson's trichrome stain. Mouse podocyte cells (MPC5) were treated with TAC and/or TGF-β1 for 48 h. The mRNA levels and protein expression of synaptopodin and Wilms' tumor 1 (WT1) were determined by real-time PCR, Western blotting and/or immunofluorescence, respectively. Flow cytometry was used to detect cell apoptosis with annexin V. Podocyte foot processes were observed under transmission electron microscopy. IgG and C3 deposition were assessed with immunofluorescence assays and confocal microscopy.Synaptopodin expression significantly decreased in MRL/lpr disease control mice, accompanied by increases in 24-h proteinuria, blood urea nitrogen, and serum creatinine. TAC, however, reduced proteinuria, improved renal function, attenuated renal pathology, restored synaptopodin expression and preserved podocyte numbers. In MPC5 cells, TGF-β1 enhanced F-actin damage in podocytes and TAC stabilized it. TAC also decreased TGF-β1-induced podocyte apoptosis in vitro and inhibited foot process fusion in MRL/lpr mice. In addition, our results also showed TAC inhibited glomerular deposition of IgG and C3.This study demonstrated that TAC reduced proteinuria and preserved renal function in LN through protecting podocytes from injury partly by stabilizing podocyte actin cytoskeleton and inhibiting podocyte apoptosis.